Total Recordable Injury and Incident Rate - Winda Trijayanthi Utama (Fakultas Kedokteran, 2020)
Indonesia is a country that has a high level of industrial development. This can be seen by the rapid growth and spread of industry, both on a small, medium, and large scale. The more rapid the industry is of course directly proportional to the emergence of challenges and problems in the industrial world. One of the challenges and problems that arise is how to deal with work accidents in a company environment. One of the efforts that can be made by companies to reduce the number of work accidents is to calculate work accidents. Calculation work accidents are fundamental in the world of occupational safety and health because the main objective of occupational safety and health is the prevention of occupational accidents and diseases. Total Recordable Injury and Incident Rate is a mathematical calculation of the total recordable incidents (above